2020
DOI: 10.1128/jb.00177-20
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Binding Protein B and Transferrin Binding Protein A2 Expand the Transferrin Recognition Range of Histophilus somni

Abstract: The bacterial bipartite transferrin receptor is an iron acquisition system that several important human and animal pathogens require for survival. It consists of the TonB-dependent transporter transferrin binding protein A (TbpA) and the surface lipoprotein transferrin binding protein B (TbpB). Curiously, the Tbps are only found in host-specific pathogens and are themselves host specific, meaning that they will bind to the transferrin of their host species but not to the transferrins of other animal species. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…In a few cases, TBPs and LBPs of bacteria can directly bind host transferrin or lactoferrin to plunder Fe 3+ into the bacterial cytoplasm under iron stress. The process is also powered by the TonB system [30,31] …”
Section: Iron Acquisition and Regulatory Strategies Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In a few cases, TBPs and LBPs of bacteria can directly bind host transferrin or lactoferrin to plunder Fe 3+ into the bacterial cytoplasm under iron stress. The process is also powered by the TonB system [30,31] …”
Section: Iron Acquisition and Regulatory Strategies Of Bacteriamentioning
confidence: 99%
“…The process is also powered by the TonB system. [30,31] Systems for acquisition of heme and ferrous iron (Fe 2+ ) More than 80% of the iron in the human body is in heme. Therefore, when bacteria infect the human body, obtaining heme is an important strategy for bacteria to uptake iron, including via direct heme transport systems, indirect heme transport systems, and the iron reductase system.…”
Section: Iron Acquisition and Regulatory Strategies Of Bacteriamentioning
confidence: 99%
“…One of the mechanisms of iron utilization required by bacterial pathogens is the direct binding of host transferrin by bacterial surface receptors [ 6 ]. The functioning of this mechanism is provided by two outer membrane proteins - transferrin-binding proteins A and B, encoded by the tbpA and tbpB genes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Histophilus somni receptors bind bovine transferrin, which in part accounts for H. somni specificity to cattle [ 7 ]. Recent studies have found that H. somni is also capable of binding sheep and goat transferrins [ 6 ]. Analysis of the complete genomes of H. somni , provided in the GenBank database, revealed that tbpA and tbpB were present in all sequences.…”
Section: Methodsmentioning
confidence: 99%
“…An exception to this can be found in Haemophilus somnus, which has been shown to possess two different systems for the acquisition of iron from transferrins of multiple species (53). It has been recently proposed that two receptors HsTbpA and HsTbpA2 work in conjunction with an SLP, HsTbpB, to broaden the transferrin recognition range to include transferrins from ovine, bovine, and caprine allowing for H. somni infection in these species (54).…”
Section: Acquiring Iron With Tbpb and Lbpbmentioning
confidence: 99%